Systemic Gifted Education: A Theoretical Introduction. (July 2017) - Ziegler, Albert; Stoeger, Heidrun
Over the past few decades, systemic thinking has gained in popularity in developmental and learning sciences. The trend has, however, shown up in gifted education research only occasionally. The aim of this article is to introduce systemic thinking to the field of giftedness and explore possibilities for its application. In the first part, a definition of a system is provided and basic concepts of systemic thinking are introduced. In the second part, a full-fledged systemic model is introduced, the actiotope model of giftedness. In the third part, implications for gifted education are elaborated. In the discussion, the authors explain (a) how systemic thinking can make a valuable contribution to gifted education, (b) why systemic thinking will complement rather than replace current approaches to gifted education, and (c) the necessity of combining systemic thinking with other empirically testable theories.